+0  
 
0
53
1
avatar

3p-+3p-+p=45

combining this brings

7p-12=45

but i originally got 5p-12=45. Because when subtracting p from 6p (i used inverse operations), the answer would be 5.

turns out inverse operations isn't used. So is inverse operaions never used when combining? is it only for solving?

 Oct 6, 2022
 #1
avatar+1015 
+1

Sorry, but 3p-+3p-+p = 45 = -p not 7p - 12.

Thus we obtain p = -45. 3p - (+3p) is distributing -1 to 3p, so it become -3p w/o the parenthesis. It turns out that -+ the minus takes priority.

 Oct 6, 2022

8 Online Users

avatar